Synthesis of 1,3-Dithienylbenzo[c]thiophene - Mendes, Paulo J. (2017)
Fused-ring thiophenes, such as benzo[c]thiophene (or isothianaphthene) derivatives have attractive electric and optical properties and can be used as monomers to build low-bandgap polymers. Benzo[c]thiophene compounds are relatively unstable and their synthesis is often laborious. The stability can be improved by the presence of aromatic heterocycles in 1 and 3 positions. For example, 1,3-dithienylbenzo[c]thiophene has been studied due to its interesting electro-optical properties.This experiment proposes the synthesis of 1,3-dithienobenzo[c]thiophene by ring closure of an o-diketone. The procedure involves three high yielding steps with minimum puri- fication procedures.